Effect of post-weld heat treatment on hardness in superduplex stainless steel astm a890/a890m-grade 6a - de Oliveira, Clélia Ribeiro; Maia, Eloá Lopes; da Fonseca, Solange Tamara; Martins, Marcelo; Díaz, Julián Arnaldo Ávila [UNESP]; Mei, Paulo Roberto (Trans Tech Publications, 2020)
Superduplex stainless steel alloy exhibit high mechanical and corrosion resistance, which main industrial application is in the petrochemical industry. The manufacture and maintenance of such equipment usually involve welding processes, followed by post-welded heat treatment and it often becomes impossible to apply heat treatments. Thereby, the purpose of this work is to verify the effect of a post-welded heat treatment on shielded metal arc welding in steel grade ASTM A890/A890M-grade 6A. The microstructure in the as-welded condition consisted of austenite, secondary austenite, and ferrite phases and, the post-welded heat treatment condition exhibited only austenite and ferrite. The hardness in the melt zone reached values of 300 HV after welding and, the value was reduced to 260 HV in the post-welded heat treatment condition.
Keywords: ASTM A890/A890M standard; Post-welded heat treatment; Superduplex stainless steels; Vickers hardness